Evaluation of transcutaneous bilirubin levels in healthy and preeclamptic pregnancies: a pilot study - Onat, Miray; Kavak, Ebru Celik; Akcabay, Cigdem; Malkan, Zubeyde; Kaya, Tugba; Batmaz, Ibrahim; Kavak, Salih Burcin (Bmc, 2025)
Background Preeclampsia is a complex, multisystem obstetric disorder characterized by heterogeneous clinical manifestations, often requiring enhanced strategies for early detection, management, and risk stratification. This study aimed to evaluate potential alterations in non-invasive transcutaneous bilirubin levels measured at various maternal body sites in pregnant women diagnosed with preeclampsia. Methods A total of 86 pregnant women who delivered at our institution were enrolled and classified into three groups: healthy pregnant women (Group 1, n = 30), women with preeclampsia (Group 2, n = 30), and women with pre-eclampsia with severe features (Group 3, n = 26). In addition to routine pre-delivery laboratory assessments, transcutaneous bilirubin levels were measured at two anatomical sites-the forehead and the abdominal skin overlying the uterine fundus-using a standard bilirubinometer. Each site was measured three times, and the mean of the three readings was recorded for analysis. Complete Blood Count and biochemical blood parameters of the women were evaluated. Relevant obstetric and demographic data were also collected and recorded. Results There were no statistically significant differences among the three groups in terms of maternal age, gravidity, parity, or body mass index (p > 0.05). Similarly, total serum bilirubin levels were comparable across the groups (Group 1: 0.45 mg/dL; Group 2: 0.39 mg/dL; Group 3: 0.44 mg/dL; p > 0.05). In contrast, transcutaneous bilirubin levels were significantly elevated in Group 3 compared to Groups 1 and 2. The mean transcutaneous bilirubin values for the forehead, uterine fundus, and overall (combined sites) were as follows: Group 1-3.07 +/- 0.85, 2.35 +/- 0.97, and 2.71 +/- 0.76; Group 2-6.09 +/- 1.94, 4.94 +/- 1.64, and 5.52 +/- 1.59; Group 3-7.12 +/- 1.81, 6.12 +/- 2.25, and 6.63 +/- 1.69, respectively. All pairwise comparisons demonstrated statistically significant differences (p < 0.05). Conclusions Transcutaneous bilirubin levels were significantly elevated in women with preeclampsia, particularly among those with severe disease. As a non-invasive, rapid, and cost-effective approach, TcB measurement may function as an adjunctive tool for the initial clinical assessment and risk stratification of preeclamptic patients.
Keywords: Preeclampsia; Serum bilirubin; Transcutaneous bilirubin; Non-invasive diagnostics